2020
DOI: 10.3390/ijerph17176039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Parents’ Knowledge about the Development of Self-Esteem in Adolescents and Their Parenting Practice on the Self-Esteem and Suicidal Behavior of Urban High School Students in Nepal

Abstract: Background: Suicide is the third leading cause of death in adolescents worldwide, self-esteem is a strong protective factor, and parents may be able to provide interventions. This cross-sectional study aimed to determine how parents can help enhance their adolescent’s self-esteem and prevent suicidal behavior among adolescents in Nepal. Methods: Self-administered questionnaires were distributed to adolescents aged 13–19 years and their parents at eight high schools in three provinces in Nepal (n = 575 pairs). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 68 publications
(154 reference statements)
1
6
0
1
Order By: Relevance
“…In this study, a few respondents highlighted how the positive family climate influenced their positive character building. They mentioned that: This study's findings are consistent with previous research (for example: Banstola et al, 2020;Sugiarti et al, 2021;Tulip et al, 2020;Smith-Adcock et al, 2019), which found that the family climate, as mediated by parenting, plays an important role in the development of character in adolescents. Other experts, such as Huang et al (2021) as well as Lin and Chiao (2020), have argued that family members will display diverse personalities influenced by their parents at home, which will be strengthened as they grow older.…”
Section: Character Buildingsupporting
confidence: 91%
“…In this study, a few respondents highlighted how the positive family climate influenced their positive character building. They mentioned that: This study's findings are consistent with previous research (for example: Banstola et al, 2020;Sugiarti et al, 2021;Tulip et al, 2020;Smith-Adcock et al, 2019), which found that the family climate, as mediated by parenting, plays an important role in the development of character in adolescents. Other experts, such as Huang et al (2021) as well as Lin and Chiao (2020), have argued that family members will display diverse personalities influenced by their parents at home, which will be strengthened as they grow older.…”
Section: Character Buildingsupporting
confidence: 91%
“…Furthermore, adolescence is the period of unique life development that is characterized by the transition from childhood to adolescence. Adulthood whereby the adolescents should adapt themselves to various changes and challenges, and this may make the adolescents susceptible to their psychosocial problems so that, in this case, the basic foundation of positive parenting from parents is required [7]. The studies also showed that support from certain reliable individuals (adults) who act responsibly will affect the comfort of life and self-esteem in adolescents [16], [22].…”
Section: Discussionmentioning
confidence: 99%
“…The parents' support in helping the adolescents when facing many problems, either in social scope or related to academic activities, will increase their self-esteem. The research data showed that the adolescents who receive warmth and are close to their parents will increase their self-esteem [7]. For the adolescents, the closeness to parents that affects the comfort, trust, and positive communication between them will make the adolescents able to have a good interaction with the surrounding environment.…”
Section: Parenting and Self-esteem In Adolescentsmentioning
confidence: 96%
“…Estudios recientes han encontrado que la falta de comunicación y apoyo familiar favorecen la aparición de conductas de riesgo en los adolescentes (Garcia et al, 2019;Perez-Gramaje et al, 2019) e incrementan el riesgo de ideación suicida (Banstola et al, 2020). Además, la evidencia reconoce la asociación de diferentes factores clínicos y psicológicos con el riesgo suicida en adolescentes, pero son pocos los estudios que han analizado la influencia del funcionamiento familiar y del apoyo parental (Dale et al, 2010;Goschin et al, 2013;Sharaf et al, 2016).…”
Section: Discussionunclassified